The Correlation Between Students’ Critical Thinking and Students’ Reading Ability at the Tenth Grade of PPTQ Muallimin Pakan Sinayan - Dini Maisarah; Hilma Pami Putri; Reflinda Reflinda; Merry Prima Dewi (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
The research was conducted since there were many problems in reading ability which were correlated with students critical thinking. Some students who had critical thinking but their reading ability was low. It can be proved by the teacher given as test reading some students with critical thinking are able to understand a reading text well, but some students who do not think critically do not understand the reading text. Some students had good reading ability but critical thinking was low. It can be proved when students are given a reading test, there are some students who are able to read the reading text well, but their critical thinking is low so they can not do the exercises well. The design of this research was correlational research. The researcher was use the quantitative approach. The population of this research was all at the tenth grade of PPTQ Muallimin Pakan Sinayan which consist of 113. The sample was 23 students taken by class X IPA Pi. The research was carried out in May 2022. The instruments of this research were questionnaire and test for measuring students critical thinking and students reading ability at the tenth grade. To find out that the students critical thinking and students reading ability correlate or not, the researcher used the Pearson Product Moment Correlation Coefficient. There were two finding of this research. The first finding was a positive and significant correlation between students critical thinking and students reading ability at the tenth grade in PPTQ Muallimin Pakan Sinayan. It means that Ha was accepted and Ho was rejected. Second finding was a enough direction correlation between students’ critical thinking and students’ reading ability at the tenth grade of PPTQ Muallimin Pakan Sinayan. The researcher found that the coefficient of correlation between students critical thinking and students reading ability at the tenth grade of PPTQ Muallimin Pakan Sinayan was 0.603. In conclusion, this research was done for finding the correlation between students critical thinking and students reading ability at the tenth grade in PPTQ Muallimin Pakan Sinayan.